Risk of stroke/systemic embolism, major bleeding, and associated costs in non-valvular atrial fibrillation patients who initiated apixaban, dabigatran, or rivaroxaban compared with warfarin in the United States medicare population: updated analysis. (2nd December 2022) - Amin, Alpesh; Keshishian, Allison; Hines, Dionne M.; Dina, Oluwaseyi; Le, Hannah; Rosenblatt, Lisa; Liu, Xianchen; Zhang, Qisu; Vo, Lien
Abstract: Objective: To provide an updated comparison of the risk and cost of stroke/systemic embolism (SE) and major bleeding between direct oral anticoagulants (DOAC: apixaban, rivaroxaban, dabigatran) and warfarin among non-valvular atrial fibrillation (NVAF) patients. Methods: Adults (≥65 years) initiating warfarin or DOACs between 1 January 2013 and 31 December 2014 were selected from the Medicare database and propensity scores matched 1:1 to balance baseline characteristics. Cox proportional hazards models were used to estimate the risks of stroke/SE and major bleeding of each DOAC vs. warfarin. Two-part models were used to compare the stroke/SE- and major bleeding-related medical costs in each matched cohort. Results: Of the 264, 479 eligible patients, 38, 740 apixaban-warfarin pairs, 76, 677 rivaroxaban-warfarin pairs, and 20, 955 dabigatran-warfarin pairs were matched. Apixaban (Hazard Ratio [HR] = 0.46; 95% Confidence Interval [CI] 0.38–0.56) and rivaroxaban (HR = 0.71; 95% CI 0.63–0.80) were associated with a significantly lower risk of stroke/SE compared to warfarin. Apixaban (HR = 0.57; 95% CI 0.51–0.63) and dabigatran (HR = 0.80; 95% CI 0.70–0.90) were associated with a significantly lower risk of major bleeding; rivaroxaban (HR = 1.14; 95% CI 1.07–1.21) was associated with a significantly higher risk of major bleeding compared to warfarin. Compared to warfarin, apixaban and rivaroxaban had significantly lower stroke/SE-related medical costs; and apixaban and dabigatran had significantly lower major bleeding-related medical costs. Conclusions: This real-world analysis showed DOACs to be associated with a lower risk of stroke/SE and major bleeding, and lower medical costs compared to warfarin. Among them, only apixaban appears to be associated with a significantly lower risk of all three outcomes collectively: stroke/SE, major bleeding, and lower related medical costs compared to warfarin.